2015
DOI: 10.1016/j.epsl.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Future sea-level rise due to projected ocean warming beneath the Filchner Ronne Ice Shelf: A coupled model study

Abstract: A general ocean circulation model is coupled with a 3D-thermodynamical ice-sheet/shelf model to simulate the response of the Filchner-Ronne Ice Shelf (FRIS, Antarctica) and coastal parts of its catchment basin to a postulated inflow of Warm Deep Water into the ice-shelf cavity on a 1000-yr timescale. Prescribed ocean warming (based on climate projections) enters the ice-shelf cavity in the up to 1500 m deep Filchner Trough and penetrates deep into the sub-ice cavity. Increasing basal melt rates induce geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Our use of a three-dimensional ocean circulation model to compute ice shelf melt rates as input for an ice dynamics model is not unique [Determann et al, 2012;Gladstone et al, 2012;Goldberg et al, 2012aGoldberg et al, , 2012bThoma et al, 2015;Asay-Davis et al, 2015], though most other studies in the literature use a variety of melt rate parameterizations that account for the regional differences in ocean temperature and the dependence of melt rates on ocean circulation in a simplified way. The most frequently used parameterizations assume a monotonically increasing function of the melt rate with depth, see, for example, Joughin et al [2010], Martin et al [2011], Pollard and DeConto [2012], and Favier et al [2014].…”
Section: Comparison With Results From a Simple Melt Rate Parameterizamentioning
confidence: 99%
“…Our use of a three-dimensional ocean circulation model to compute ice shelf melt rates as input for an ice dynamics model is not unique [Determann et al, 2012;Gladstone et al, 2012;Goldberg et al, 2012aGoldberg et al, , 2012bThoma et al, 2015;Asay-Davis et al, 2015], though most other studies in the literature use a variety of melt rate parameterizations that account for the regional differences in ocean temperature and the dependence of melt rates on ocean circulation in a simplified way. The most frequently used parameterizations assume a monotonically increasing function of the melt rate with depth, see, for example, Joughin et al [2010], Martin et al [2011], Pollard and DeConto [2012], and Favier et al [2014].…”
Section: Comparison With Results From a Simple Melt Rate Parameterizamentioning
confidence: 99%
“…One of the most sensitive regions of the WAIS to potential ocean warming is the Weddell Sea (WS) sector Wright et al, 2014). Ocean modelling studies show that changes in present ocean circulation could bring warm ocean water into direct contact with the grounding lines at the base of the Filchner-Ronne Ice Shelf (FRIS) (Hellmer et al, 2012;Wright et al, 2014;Martin et al, 2015;Ritz et al, 2015;Thoma et al, 2015), which would act in a manner similar to the ocean-induced basal melting under the Pine Island Glacier ice shelf (Jacobs et al, 2011). Enhanced melting of the FRIS could lead to a decrease in the buttressing support to the upstream grounded ice, causing enhanced flow to the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced melting of the FRIS could lead to a decrease in the buttressing support to the upstream grounded ice, causing enhanced flow to the ocean. A recent modelling study, using a general ocean circulation model coupled with a 3-D thermodynamic ice-sheet model, simulated the inflow of warm ocean water into the Filchner-Ronne Ice Shelf cavity on a 1000-year timescale (Thoma et al, 2015). A second modelling study, this time using an ice-sheet model only, indicated that the Institute and Möller ice streams are highly sensitive to melting at the grounding lines, with grounding-line retreat up to 180 km possible across the Institute and Möller ice streams .…”
Section: Introductionmentioning
confidence: 99%
“…20, Timmermann and Hellmer 2013). The associated thickness decrease has severe consequences for the buttressing potential of the ice shelf and the dynamics of the ice streams mainly draining East Antarctica (Thoma et al 2015). The increase in glacial meltwater additionally freshens the southern Weddell Sea continental shelf, contributing to a further decline of the shelf water density.…”
Section: Freshwater Input Through Ice Shelf Basal Meltingmentioning
confidence: 99%